Dihydropyrimidine dehydrogenase and fluoropyrimidines: a review of current dose adaptation practices and the impact on the future of personalized medicine using 5-fluorouracil. (December 2013) - Boisdron-Celle, Michèle; Biason, Paola; Gamelin, Erick; Morel, Alain
SUMMARY 5-fluorouracil (5-FU) is widely used in chemotherapeutic treatments of solid tumors. However, adverse events after its administration occur in about 30% of patients. Dihydropyrimidine dehydrogenase (DPD) is the rate-limiting enzyme in the 5-FU catabolic pathway: several studies have focused on its genetics and/or pharmacokinetics in order to explain the wide interpatient variability in the DPD activity, including the rare event of its complete absence of activity. The pretreatment screening for DPD activity with a multiparametric approach (genotyping, phenotyping, clinico–pathological characteristics) shows the greatest specificity and sensitivity to avoid severe early-onset toxicity to fluoropyrimidines. In addition, using the pharmacokinetics of 5-FU, the dose adaptation can be used to properly dose each cycle for optimal efficacy and reduction of early-onset toxicities.